Learning English as a second language at the university level in Jordan: motivation, self-regulation and learning environment perceptions - Alzubaidi, E.; Aldridge, Jill; Khine, M. (Kluwer Academic Publishers, 2014)
The overarching aim of this study was to investigate students’ perceptions of the learning environment and whether these influenced their motivation and self-regulation in learning English as a second language at the university level in Jordan. Our sample involved 994 students, drawn from 13 schools, within three faculties (humanities, health sciences and engineering) of one university. The collection of data involved the administration of two surveys: one to assess students’ perceptions of the learning environment and another to assess students’ motivation and self-regulation in learning English as a second language. The results of analyses strongly supported the reliability and validity of the surveys when used at the university level in Jordan, thereby providing confidence in the results of the present study. Simple correlation and multiple regression analysis were used to examine the influence of students’ perceptions of the learning environment of English language classes on self-reports of motivation and self-regulation. Statistically significant (p < 0.05) simple correlations were found between students’ perceptions of their learning environment and their motivation and self-regulation. The regression weights (ß) indicated that scales of the learning environment were positively, statistically significantly (p < 0.05) and independently related to the motivation and self-regulation outcomes.